Evidence-Based Approaches to the Prevention and Treatment of Nsaid-Induced Gastrointestinal Injury - o’g’li, Raupov Abdurahmon Ortiq (American Journal of Bioscience and Clinical Integrity, 2025)
At present, the management of erosive and ulcerative lesions of the upper gastrointestinal tract (GIT) is a complex clinical challenge, particularly in high-risk patients with cardiovascular and vascular comorbidities receiving antiplatelet and anticoagulant therapy. Despite advances in pharmacological treatment, including H₂-receptor blockers and proton pump inhibitors (PPIs), the incidence of upper gastrointestinal bleeding (UGIB) continues to rise. H₂-receptor blockers provide limited, short-lived acid suppression and carry risks such as tolerance, rebound acid hypersecretion, and potential ischemic complications. PPIs, including omeprazole and pantoprazole, offer superior and sustained acid suppression, with pantoprazole demonstrating the longest duration of effect and lowest potential for drug–drug interactions, making it particularly suitable for critically ill patients. In patients undergoing cardiac or aortic surgery, postoperative UGIB represents a serious complication, often necessitating urgent endoscopic intervention as the preferred method for hemostasis and prevention of rebleeding. Endoscopic techniques include injection therapy, physical methods (electrocoagulation, laser), mechanical methods (clipping), ulcer surface protection, cryotherapy, and adhesive applications. Proper selection of pharmacological and endoscopic therapies, considering drug–drug interactions, patient comorbidities, and procedural risks, is essential for improving clinical outcomes in this high-risk population.